Differences in left ventricular and left atrial function assessed during breath-holding and breathing. Issue 141 (August 2021) - Reiter, Clemens; Reiter, Ursula; Kräuter, Corina; Nizhnikava, Volha; Greiser, Andreas; Scherr, Daniel; Schmidt, Albrecht; Fuchsjäger, Michael; Reiter, Gert
Highlights: LV systolic and diastolic function parameters differ between inspiratory breath-holding and free breathing acquisition. Left atrial volumetric function parameters differ between inspiratory breath-holding and free breathing acquisition. Differences between inspiratory breath-holding and breathing functional parameters show considerable variations within individuals. Abstract: Purpose: To analyze differences in systolic and diastolic left ventricular (LV) as well as left atrial (LA) function parameters obtained from identical cardiac magnetic resonance (MR) imaging techniques during inspiratory breath-holding and breathing (breath-hold to breathing differences). Method: 56 subjects without signs of heart failure (23/33 male/female, age 58 ± 14 years) underwent 3 T MR cine real-time and transmitral phase contrast imaging with the same spatial and temporal resolution during inspiratory breath-holding and free breathing. LV and LA volumetric function parameters were derived from segmentation of cine series, transmitral peak velocities and early-diastolic myocardial peak velocity from phase contrast series. Corresponding breath-hold and breathing parameters were compared by Bland-Altman analysis; repeatability of breath-hold and breathing measurements was quantified by variance component analysis. p < 0.05 was regarded as statistically significant. Results: Mean differences between results obtained during inspiratory breath-holding vs. breathing were significant for LV volumetric function (end-diastolic volume=−7 mL, p = 0.002; end-systolic volume=−7 mL, p < 0.001; ejection fraction = 3 %, p < 0.001; peak ejection rate = 22 mL/s, p = 0.002; early-diastolic peak filling rate=−34 mL/s, p = 0.025), LA volumetric function (maximum volume=-6 mL, p < 0.001; total ejection fraction=-4%, p < 0.001; active ejection fraction=-2%, p = 0.013; before contraction ejection fraction=-4%, p < 0.001) and early-diastolic velocities (transmitral=-6 cm/s, p < 0.001; tissue velocity=-1.8 cm/s, p < 0.001). Standard deviations of breath-hold-to-breathing differences exceeded the corresponding repeatabilities of breath-hold and breathing measurements. Conclusions: Systolic and diastolic LV and LA function parameters acquired during inspiratory breath-holding and breathing differ, and large inter-individual breath-hold-to-breathing variations are possible. Thus, the breathing state should be taken into account, especially when comparing results in patient follow-up acquired in different respiratory states.